Jack Ryan : Shadow recruit - Branagh, Kenneth; Cozad, Adam; Koepp, David; Neufeld, Mace; Di Bonaventura, Lorenzo; Vahradian, Mark; Barron, David (Film producer); Pine, Chris, 1980-; Costner, Kevin; Knightley, Keira, 1985-; Clancy, Tom, 1947-2013.; Paramount Pictures Corporation; et al. (Hollywood, CA : Paramount, 2014)
A global action thriller set in the present day. This original story follows a young Jack as he uncovers a financial terrorist plot. When Ryan believes he's uncovered a Russian plot to collapse the United States economy, he goes from being an analyst to becoming a spy and must fight to save his own life and those of countless others, while also trying to protect the thing that's more important to him than anything, his relationship with his fiance Cathy.
Originally released as a motion picture in 2014.
Based on characters created by Tom Clancy.
Music, Patrick Doyle ; editor, Martin Walsh ; director of photography, Haris Zambarloukous.
Chris Pine, Kevin Costner, Keira Knightley, Kenneth Branagh.
MPAA Rating: PG-13; for sequences of violence and intense action, and brief strong language.
DVD, NTSC region 1, widescreen presentation; 5.1 Dolby Digital.
Keywords: Ryan, Jack, Jr. (Fictitious character) -- Drama; Terrorism -- Drama; Spies -- Drama; Man-woman relationships -- Drama; Action and adventure films; Drama; Feature films; Thrillers (Motion pictures); Video recordings for people with visual disabilities; Video recordings for the hearing impaired